2001
DOI: 10.1021/jp010894p
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Bonding in Dinuclear Oxoanions of V, Nb, Ta, Mo, and W

Abstract: The structure and bonding in [M2O7] n - anions of the early transition metals V, Nb, Ta, Mo, and W have been investigated by density-functional methods. Several molecular conformations have been tested in geometry optimizations, and systems with a linear M−O−M bridge have been the only structures obtained for V, Nb, and Ta, and the most stable configurations for Mo and W. Molecular-orbital analysis has indicated that multiple bonds are formed between the metal and both bridging (Ob) and terminal (Ot) oxygen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 35 publications
8
28
0
Order By: Relevance
“…However, (relative) Mayer bond indexes and Mulliken charges can nonetheless provide valuable chemical information, if uniformity and consistency of basis set are maintained. 39 The Mulliken analysis is consistent with the internal structure of the molecular orbital formalism and we have shown 19 that the values it predicts for polyoxometalates are qualitatively consistent with those based on other schemes. We have shown previously 39 that for many bonds, such as those between a central atom and ligands, the bond order can be expressed as a sum over symmetry species G,…”
Section: Computational and Analytical Approachsupporting
confidence: 81%
See 2 more Smart Citations
“…However, (relative) Mayer bond indexes and Mulliken charges can nonetheless provide valuable chemical information, if uniformity and consistency of basis set are maintained. 39 The Mulliken analysis is consistent with the internal structure of the molecular orbital formalism and we have shown 19 that the values it predicts for polyoxometalates are qualitatively consistent with those based on other schemes. We have shown previously 39 that for many bonds, such as those between a central atom and ligands, the bond order can be expressed as a sum over symmetry species G,…”
Section: Computational and Analytical Approachsupporting
confidence: 81%
“…The developments and advances in density functional (DF) theory and effective core potentials or frozen cores have provided both the accuracy and computational economy necessary to model the structures and properties of polyoxometalates. Most of the first-principle studies related to polyoxoanions have been carried out by Poblet, Bénard and co-workers, [6][7][8][9][10][11][12][13][14][15][16][17] initially at the Hartree-Fock (HF) and latterly at density functional (DF) levels of theory, and by Bridgeman and Cavigliasso, [18][19][20][21][22][23][24][25][26][27] and Borshch and coworkers [28][29][30] at the DF level. This computational work has demonstrated that it is possible to accurately model many properties of polyoxometalates, including structures, vibrational spectra and aspects of reactivity such as redox behaviour and protonation sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The agreement between the crystallographic and calculated bond lengths is reasonable at all levels. In keeping with previous computational studies of POMs, [24][25][26] bond lengths are over estimated particularly for terminal and heteroatom-oxygen bonds. The MoÀO 2c bond lengths are well reproduced at all levels.…”
Section: Computational Approachsupporting
confidence: 73%
“…The MoÀO 2c bond lengths are well reproduced at all levels. As we have noted previously, [6,25] the LDA approach appears best able to reproduce solid state bond lengths. This presumably reflects a compensation for the lack of the stabilizing crystal field in pseudo-gas phase calculations by the overbinding associated with the local density method.…”
Section: Computational Approachsupporting
confidence: 61%